Evaluation of isocyanate and blocked isocyanate bonding systems in selective fibre/elastomer composites - Guha A; Ghosh A K; Ghosh R N (Indian Journal of Natural Rubber Research, 1993)
This paper investigates the use of a commercially available carpolactam blocked methylenebis-(4-phenylisopcyanate) along with RFL as a bonding agent for cord/fabrics made with nylon-66, polyester and aramid under different conditions, with special reference to the influence of heat and steama ageing on adhesion. An attempt has also been made to compare the present bonding agent with the conventional dipping techniques. All the dipping systems studied showed good adhesion with NR and SBR compounds. In most of the dipping systems the SBR compound had better adhesion compared to the NR compound. The blocked isocyanate/RFL adhesive system showed an appreciable drop in H-pullout adhesion compared to unblocked isocyanate and RFL system. However, peel adhesion was remarkably better for the former with both compounds in the case of nylon fabrics. No significant change in adhesion was observed by the incorporation of epoxy compounds in blocked isocyanate/RFL adhesive system. Excellent adhesion retention was observed after ageing of fibres treated with blocked isocyanate/RFL system compared to unblocked isocyanate/RFL system in both the rubber compounds.
Keywords: Adhesion strength; Adhesion strength; Composites; Composites; Cord/fabric-rubber bonding; Cord/fabric-rubber bonding; Natural rubber; Natural rubber; Styrene-butadiene rubber; Styrene-butadiene rubber